Brake pad for coating carbon ceramic brake disc and preparation method of brake pad

Through specific components of reinforced fibers and inorganic fillers, brake pads for coated carbon ceramic brake discs are prepared, which solves the corrosion problem between brake pads and cast iron or cast steel brake discs in the prior art, and improves friction performance and service life. , achieving the goal of matching with coated carbon ceramic brake discs and green environmental protection.

CN119122954APending Publication Date: 2024-12-13BEIJING TIANYISHANGJIA NEW MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411190953.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The matching of existing brake pads with cast iron or cast steel brake discs has problems with brake disc rust during braking, and the base metal may be transferred or bonded under high temperature conditions, affecting friction performance and service life.

Method used

Reinforced fibers composed of steel fibers and basalt fibers of a specific weight ratio and inorganic fillers composed of magnesium hydroxide, silicon carbide, tungsten carbide, dianthamn antimony trisulfide, nano-silicon powder, and barium sulfate were prepared to produce a relative density of 3.3±0.1g The brake pads for coated carbon ceramic brake discs of /cm3 can improve the shear strength, material coverage and thermal expansion performance of the brake pads through specific mixing, pressing, curing and ablation processes.

Benefits of technology

It achieves matching with coated carbon ceramic brake discs, reduces friction performance attenuation during high-speed and high-temperature braking, avoids brake disc rust, extends the service life of the brake disc, and achieves the goal of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of friction materials, and particularly discloses a brake pad for a coated carbon-ceramic brake disc and a preparation method of the brake pad. The invention discloses a brake pad for a coated carbon ceramic brake disc. The brake pad comprises, by weight, 5-10 parts of polyimide resin, 10-20 parts of red copper scraps, 2-5 parts of white corundum, 5-10 parts of potassium hexatitanate lamellar crystals, 5-10 parts of iron-nickel alloy powder, 5-9 parts of titanium alloy powder, 13-25 parts of reinforced fibers and 30-57 parts of inorganic filler. The reinforced fibers are composed of steel fibers and basalt fibers; the inorganic filler is prepared from magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of (5-9): (5-9): (2-5): (5-10): (5-12): (8-12). The prepared brake pad is high in shear strength and material coverage rate and excellent in thermal expansion and compression strain performance, and the brake pad material has excellent friction performance and NVH performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of friction materials, and in particular to a brake pad for a coated carbon-ceramic brake disc and a preparation method thereof. Background Art

[0002] In the past 20 years, with the vigorous development of transportation, friction materials have developed particularly rapidly, and many new friction materials and brake discs have emerged, which are widely used in various types of engineering machinery and transportation equipment. The trend of scientific and technological development in the 21st century is high speed, environmental protection and energy saving. In order to adapt to the needs of this new situation, higher requirements are put forward for the comprehensive performance of friction pair materials.

[0003] Organic friction materials have evolved from asbestos friction materials to asbestos-free, pollution-free, and high-speed. With the development and progress of society, people have higher and higher requirements for vehicles, such as high speed, heavy load, safety and reliability, comfortable ride, easy operation, low energy consumption, and pollution-free. The vehicle industry has also shown a booming and diversified development trend.

[0004] At present, the brake pads in use are mostly matched with gray cast iron brake discs and cast steel brake discs, which are not conducive to the development of friction pairs. It is necessary to accelerate the research and application of friction pairs. The efficiency of reducing 1KG of unsprung mass is equivalent to reducing about 10-15KG of sprung mass. When the sprung mass is constant, it is necessary to reduce the unsprung mass as much as possible, which can improve the acceleration, stability and handling of the vehicle. The reason why aluminum alloy wheels and aluminum alloy suspension components (tie rods, rocker arms, etc.) are widely used is mainly because they can effectively reduce the unsprung mass.

[0005] Coated carbon ceramic brake discs are made by adding a coating to the carbon ceramic disc substrate and then high-temperature siliconizing. Carbon ceramic discs are made on the basis of carbon fiber preforms using a high-temperature chemical vapor deposition (CVI) production process. The weight of coated carbon ceramic brake discs is only 35% of that of cast iron brake discs, thereby improving starting acceleration and braking response speed.

[0006] In summary, based on the excellent performance and lightweight characteristics of coated carbon-ceramic brake discs, it is of great significance to develop brake pads that match them to realize coated carbon-ceramic brake friction pairs. Summary of the invention

[0007] In order to solve the above technical problems, the present application provides a brake pad for a coated carbon-ceramic brake disc and a preparation method thereof.

[0008] The present application provides a brake pad for a coated carbon ceramic brake disc, specifically comprising the following components in parts by weight: 5-10 parts of polyimide resin, 10-20 parts of copper chips, 2-5 parts of white corundum, 5-10 parts of potassium hexatitanate platelets, 5-10 parts of iron-nickel alloy powder, 5-9 parts of titanium alloy powder, 13-25 parts of reinforcing fiber, and 30-57 parts of inorganic filler;

[0009] The reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 10-20:3-5;

[0010] The inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 5-9:5-9:2-5:5-10:5-12:8-12.

[0011] The technical solution provided by the present application uses steel fiber and basalt fiber in a specific weight ratio to form reinforcing fibers, and inorganic fillers composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder, and barium sulfate in a specific weight ratio. The prepared brake pad for the coated carbon ceramic brake disc has a relative density of 3.3±0.1g / cm3, shear strength ≥6.2MPa, material coverage ≥95%, Rockwell hardness 89-97HRR, thermal expansion ≤1.0%, room temperature compression strain ≤0.08%, high temperature compression strain ≤1.5%, friction coefficient meets the requirements, and NVH performance reaches AA level. The brake pad for the coated carbon ceramic brake disc prepared by the technical solution provided by the present application has excellent performance.

[0012] Preferably, the amount of the reinforcing fiber is 17-21 parts.

[0013] Preferably, the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 13-17:3.5-4.5.

[0014] Preferably, the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 15:4.

[0015] In some specific embodiments, the weight ratio of steel fiber and basalt fiber in the reinforcing fiber can be 10:3, 10:3.5, 10:4, 10:4.5, 10:5, 13:3, 13:3.5, 13:4, 13:4.5, 13:5, 15:3, 15:3.5, 15:4, 15:4.5, 15:5, 17:3, 17:3.5, 17:4, 17:4.5, 17:5, 20:3, 20:3.5, 20:4, 20:4.5, 20:5.

[0016] In a specific embodiment, in the reinforcing fiber, the weight ratio of steel fiber and basalt fiber can also be 10-13:3, 10-13:3.5, 10-13:4, 10-13:4.5, 10-13:5, 13:3-4, 13-15:3.5, 13-15:4, 13-15:4.5, 13-15:5, 15:3-4, 15:3.5-4.5, 15:4-5, 15-17:4.5, 15-17:5, 17:3-4, 17:3.5-4.5, 17:4-5, 17-20:4.5, 17-20:5, 20:3-4, 20:3.5-4.5, 20:4-5, 20:4.5-5, 15-20:5.

[0017] Through experimental analysis, it can be known that the present application utilizes the steel fiber and basalt fiber in the above weight ratio to form the reinforcing fiber, which can further improve the performance of the reinforcing fiber.

[0018] Preferably, the amount of the inorganic filler is 40-48 parts.

[0019] Preferably, the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 6-8:6-8:3-4:7-9:7-10:9-11.

[0020] Preferably, the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 7:8:3.5:8:8:10.

[0021] In some specific embodiments, among the inorganic fillers, magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder, and barium sulfate can also be: 5-7:5:2:5:5:8, 6:6-8:3:7:7:9, 6:8:4:7-9:10:11, 8:6:3:7-9:7:9, 9:9:5:10:12:9-12.

[0022] In a specific embodiment, among the inorganic fillers, magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder, and barium sulfate can be: 5:5:2:5:5:8, 6:6:3:7:7:9, 6:8:4:9:10:11, 8:6:3:7:7:9, 9:9:5:10:12:12.

[0023] Through experimental analysis, it can be known that the inorganic filler composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in the above weight ratio can further improve the performance of the reinforcing fiber.

[0024] In a second aspect, the present application provides a method for preparing a brake pad for the above-mentioned coated carbon-ceramic brake disc, which specifically comprises the following steps:

[0025] Mix all the raw materials according to the ratio, and the mixing time is 30-70 minutes;

[0026] Pressing: Place the mixture in a mold and press it at a pressure of 20-30Mpa for 420-720s.

[0027] Curing: Heat the pressed blank to 260-300℃ and cure for 10-15h, then machine it to the appropriate size;

[0028] Ablation: The sample is subjected to surface ablation treatment at an ablation temperature of 600-650°C.

[0029] Preferably, the pressing conditions are: pressing pressure is 23-27Mpa, and pressing time is 540-600s.

[0030] Preferably, the curing condition is: heating the pressed blank to 270-290° C. and curing for 12-13 hours.

[0031] In summary, the technical solution of this application has the following effects:

[0032] The present application develops a new brake pad that is better matched with a coated carbon-ceramic brake disc, realizes a coated carbon-ceramic brake friction pair, has a lower friction performance attenuation rate during high-speed and high-temperature braking, reduces the unsprung mass, solves the problem of brake disc rust during the braking process of the cast iron or cast steel brake disc friction pair, completely avoids the transfer and adhesion of the base metal of the brake pad during high-temperature braking with an ordinary cast iron or cast steel brake disc, realizes the matching of the brake pad and the coated carbon-ceramic brake disc, and extends the service life of the brake disc, achieving the goal of green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a friction performance test curve of the brake pad for the coated carbon-ceramic brake disc in Example 1.

[0034] Figure 2 This is a friction performance test curve of the brake pad for the coated carbon-ceramic brake disc in Example 1.

[0035] Figure 3 This is a graph showing the NVH performance test results of the brake pad for the coated carbon-ceramic brake disc in Example 1.

[0036] Figure 4 This is a curve chart of the NVH performance test data of the brake pad for the coated carbon-ceramic brake disc in Example 1. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with examples, comparative examples and performance testing experiments. These examples should not be construed as limiting the scope of protection claimed in the present application.

[0038] Example

[0039] Examples 1-5

[0040] Embodiments 1-5 respectively provide a brake pad for a coated carbon-ceramic brake disc.

[0041] The difference between the above embodiments is that the amount of each component in the brake pad for coated carbon-ceramic brake disc is different, as shown in Table 1.

[0042] The preparation method of the brake pad for the coated carbon ceramic brake disc in the above embodiment is as follows:

[0043] The raw materials of each component are fully mixed according to the ratio, and the mixing time is 50 minutes; wherein, the reinforcing fiber is composed of steel fiber and basalt fiber in a weight ratio of 15:4; the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 7:8:3.5:8:8:10;

[0044] Pressing: Place the mixture in a mold* and press at a pressure of 25Mpa for 580s;

[0045] Curing: The pressed blank is heated to 280°C for curing for 12.5 hours and then machined to the appropriate size;

[0046] Ablation: The sample is subjected to surface ablation treatment at an ablation temperature of 625°C.

[0047] Table 1 Amount of each component in the brake pad for coated carbon ceramic brake disc in Examples 1-5 and Comparative Examples 1-2

[0048]

[0049] Embodiment 6-9

[0050] Embodiments 6-9 respectively provide a brake pad for a coated carbon-ceramic brake disc.

[0051] The difference between the above embodiment and embodiment 1 is that the composition of the reinforcing fibers is different, as shown below.

[0052] In Example 6: the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 10:5 (ie, 2:1).

[0053] In Example 7: the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 13:4.5.

[0054] In Example 8: the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 17:3.5.

[0055] In Example 9: the reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 20:3.

[0056] The other raw materials and their amounts in the above embodiment and the preparation method of the brake pad for the coated carbon ceramic brake disc are the same as those in embodiment 1.

[0057] Examples 10-13

[0058] Embodiments 10-13 respectively provide a brake pad for a coated carbon-ceramic brake disc.

[0059] The difference between the above embodiment and embodiment 1 is that the composition of the inorganic filler is different, as shown below.

[0060] In Example 10: the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 5:9:2:10:5:8.

[0061] In Example 11: the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 9:5:5:5:12:12.

[0062] In Example 12: the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 6:8:3:9:7:9.

[0063] In Example 13: the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 8:6:4:7:10:11.

[0064] The other raw materials and their amounts in the above embodiment and the preparation method of the brake pad for the coated carbon ceramic brake disc are the same as those in embodiment 1.

[0065] Comparative Example

[0066] Comparative Example 1-2

[0067] Comparative Examples 1-2 respectively provide a brake pad for a coated carbon-ceramic brake disc.

[0068] The difference between the comparative example and Example 1 is that the amounts of the components in the brake pad for the coated carbon-ceramic brake disc are different, as shown in Table 1.

[0069] The other raw materials and their amounts in the above comparative example and the preparation method of the brake pad for the coated carbon-ceramic brake disc are the same as those in Example 1.

[0070] Comparative Examples 3-6

[0071] Comparative Examples 3-6 respectively provide a brake pad for a coated carbon-ceramic brake disc.

[0072] The difference between the comparative example and Example 1 is that the amounts of the components in the brake pad for the coated carbon-ceramic brake disc are different, as shown below.

[0073] In Comparative Example 3: the reinforcing fibers consist of aluminum fibers and basalt fibers in a weight ratio of 15:4.

[0074] In Comparative Example 4: the reinforcing fibers consist of steel fibers and basalt fibers in a weight ratio of 25:3.

[0075] In Comparative Example 5: the inorganic filler is composed of calcium carbonate, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 7:8:3.5:8:8:10.

[0076] In Comparative Example 6: the inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 2:10:7:2:4:13.

[0077] The other raw materials and their amounts in the above comparative example and the preparation method of the brake pad for the coated carbon-ceramic brake disc are the same as those in Example 1.

[0078] Performance testing

[0079] Test results: as shown in Table 2.

[0080] (1) Material properties

[0081] Relative density test method: GB 1033.1;

[0082] Shear strength test method: GB 22309;

[0083] Material coverage test method: GB / T 31565-2015;

[0084] Rockwell hardness test method: GB 5766-2007-T;

[0085] Thermal expansion test method: GB 22310;

[0086] Compression strain test method: GB / T 22311.

[0087] Table 2 Material performance test results of brake pads for coated carbon ceramic brake discs in the embodiments and comparative examples

[0088]

[0089]

[0090] Combined with the test results in Table 2, the relative density of the brake pad for the coated carbon ceramic brake disc prepared by the technical solution provided by the present application is 3.3±0.1g / cm 3 , shear strength ≥ 6.2MPa, material coverage ≥ 95%, Rockwell hardness 89-97HRR, thermal expansion ≤ 1.0%, room temperature compression strain ≤ 0.08%, high temperature compression strain ≤ 1.5%. The above test results show that the coated carbon ceramic brake disc brake pad prepared by the technical solution provided by this application has excellent performance.

[0091] (2) Friction performance

[0092] The friction performance of the brake pad for the coated carbon ceramic brake disc prepared in Example 1 was tested on a bench according to the requirements of the "SAE J2522" standard, with the maximum test temperature being 560°C. The test results are as follows: Figure 1-2 The experimental results are shown in Table 3. The nominal friction coefficient is 0.44 (the average value of the friction coefficients under the first decay, high temperature and second decay conditions), the minimum friction coefficient is 0.43 (the minimum value of the friction coefficients under the first decay, high temperature and second decay conditions), and the highway braking friction coefficient is 0.35.

[0093] Table 3 Experimental results of friction performance of brake pads for coated carbon ceramic brake discs in Example 1

[0094]

[0095] (3) NVH performance test results

[0096] The NVH performance of the brake pad for the coated carbon ceramic brake disc prepared in Example 1 was tested according to the "SAE J2521" standard. The results are as follows: Figure 3 As shown, the data processing curve is as follows Figure 4 As shown, it reaches AA level; that is, the decibel values ​​at each stage meet the following requirements: the absolute percentage of the Overall decibel value ≥ 70db ≤ 3%, and the absolute percentage of the Overall decibel value ≥ 80db ≤ 1%. This result shows that the brake pads for coated carbon ceramic brake discs prepared in this application can ensure that vehicles do not generate braking noise under urban road conditions.

[0097] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A brake pad for a coated carbon-ceramic brake disc, characterized in that: Specifically, it includes the following components in parts by weight: 5-10 parts of polyimide resin, 10-20 parts of copper chips, 2-5 parts of white corundum, 5-10 parts of potassium hexatitanate platelets, 5-10 parts of iron-nickel alloy powder, 5-9 parts of titanium alloy powder, 13-25 parts of reinforcing fiber, and 30-57 parts of inorganic filler; The reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 10-20:3-5; The inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 5-9:5-9:2-5:5-10:5-12:8-12.

2. The brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The amount of the reinforcing fiber is 17-21 parts.

3. The brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 13-17:3.5-4.

5.

4. The brake pad for a coated carbon-ceramic brake disc according to claim 3, characterized in that: The reinforcing fibers are composed of steel fibers and basalt fibers in a weight ratio of 15:

4.

5. The brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The amount of the inorganic filler is 40-48 parts.

6. The brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The inorganic filler is composed of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 6-8:6-8:3-4:7-9:7-10:9-11.

7. The brake pad for a coated carbon-ceramic brake disc according to claim 6, characterized in that: The inorganic filler consists of magnesium hydroxide, silicon carbide, tungsten carbide, antimony trisulfide, nano silicon powder and barium sulfate in a weight ratio of 7:8:3.5:8:8:

10.

8. The method for preparing a brake pad for a coated carbon-ceramic brake disc according to any one of claims 1 to 7, characterized in that: The specific steps include: Mix all the raw materials according to the ratio, and the mixing time is 30-70 minutes; Pressing: Place the mixture in a mold and press it at a pressure of 20-30Mpa for 420-720s. Curing: Heat the pressed blank to 260-300℃ and cure for 10-15h, then machine it to the appropriate size; Ablation: The sample is subjected to surface ablation treatment at an ablation temperature of 600-650°C.

9. The method for preparing a brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The pressing conditions are: pressing pressure of 23-27 MPa, pressing time of 540-600 s.

10. The method for preparing a brake pad for a coated carbon-ceramic brake disc according to claim 1, characterized in that: The curing conditions are as follows: heating the pressed blank to 270-290° C. and curing for 12-13 hours.